Tectonic interactions during rift linkage: insights from analog and numerical experiments - T. C. Schmid; S. Brune; S. Brune; A. Glerum; G. Schreurs (Solid Earth, 2023)
Continental rifts evolve by linkage and interaction of adjacent individual segments. As rift segments propagate, they can cause notable re-orientation of the local stress field so that stress orientations deviate from the regional trend. In return, this stress re-orientation can feed back on progressive deformation and may ultimately deflect propagating rift segments in an unexpected way. Here, we employ numerical and analog experiments of continental rifting to investigate the interaction between stress re-orientation and segment linkage. Both model types employ crustal-scale two-layer setups wherein pre-existing linear heterogeneities are introduced by mechanical weak seeds. We test various seed configurations to investigate the effect of (i) two competing rift segments that propagate unilaterally, (ii) linkage of two opposingly propagating rift segments, and (iii) the combination of these configurations on stress re-orientation and rift linkage. Both the analog and numerical models show counterintuitive rift deflection of two sub-parallel propagating rift segments competing for linkage with an opposingly propagating segment. The deflection pattern can be explained by means of stress analysis in numerical experiments wherein stress re-orientation occurs locally and propagates across the model domain as rift segments propagate. Major stress re-orientations may occur locally, which means that faults and rift segment trends do not necessarily align perpendicularly to far-field extension directions. Our results show that strain localization and stress re-orientation are closely linked, mutually influence each other, and may be an important factor for rift deflection among competing rift segments as observed in nature.